Factors Influencing First-Year Students’ Acceptance of University-Managed Social Media Marketing - Megawati Putri Emal HS; Arif Hartono (Eduvest - Journal of Universal Studies, 2025)
This study aims to investigate the impact of college social media marketing on first-year students. In higher education, social media marketing activities mainly focus on creating or building brand equity. This study uses TAM theory. The samples in this study were first-year students (freshmen) of a private university in Yogyakarta. There were 190 data collected and analyzed using PLS-SEM with SmartPLS 4. The results of this study reveal that motivation, ease of use have a positive and significant effect on the intention to follow social media. Intention to follow social media has a positive and significant effect on social media effectiveness and university social media acceptance. Meanwhile, usefulness was found to have a negative influence on the intention to follow university social media. In addition to expanding the study of social media marketing in higher education, this research also offers insights related to the application of social media as a marketing medium for higher education.